Pengaruh Profitabilitas, Debt Default, dan Pertumbuhan Perusahaan terhadap Opini Audit Going Concern - Tegar, Glorious (Jurnal Keuangan dan Perbankan, 2023)
Business industry can be linked to become a reference for the condition of country's economic status. Giving a going concern audit opinion can help company’s stakeholders in ensuring the sustainability of the company in the next year from the date of the audited financial statements. This can help the company to make decisions easier. This research was taken during the Covid-19 pandemic, which shows that there are companies that have suffered losses due to the pandemic and can be seen in the going concern audit opinion on the company's financial statements. Auditors are expected to be aware of the factors and potential problems that can arise and affect the sustainability of the company. These include the influence of profitability, debt default and company growth.